DISCUSSION OF SCIENCE ETHICS IN ISLAM: Reflections on Harun Nasution's Controversial Ethical Thought - Abdul Fattah (Direktorat Pondok Pesntren Universitas Islam Indonesia, 2020)
This article intends to examine the concept of scientific ethics in Islamwith a focus on the thoughts of Harun Nasution.Harun Nasution is acontroversial Islamic reformer. His idea was born as a response toand against the traditional ideas that developed at that time, evenHarun Nasution dared to go against the flow of traditional thoughtethics that had long been rusty and difficult to remove. The emphasisof this paper is on the presentation of Harun Nasution's progressivethinking in various main issues in the study of Islamic ethical thought,such as the idea of progress, coexistence between the Absolute-Textual (qath'i) and relative-contextual (zhanni) regions as afoundation the development of science in Islam, rational andtraditional categorization, inclusive attitudes: accepting culture orknowledge from outside, freedom and development mentality: freedomof thought and action, cosmology: belief in causality as a source ofsuccess, moral problems and Harun Nasution's criticism ofmaterialistic / hedonistic culture. This paper is presented consideringthat in a dynamic society, scientific ethics and community educationplay a role in determining the existence and development of society.Likewise with the role of scientific and educational ethics which is oneform of manifestation of the ideals of Islamic life to preserve, transferand instill (internalization) and transform Islamic values to thepersonal of the next generation, so that cultural-religious values areaspirated in society over time.